Patient’s Knowledge of Drug-Related Cost Information in Saudi Arabia - Alomi, Yousef Ahmed; Alaskari, Dima Ahmad; Almelf, Malak Mohammad; Badawi, Dima Ali; Alshihri, Abdullah Mohammad (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the Patient’s Knowledge of medicines related cost information in Saudi Arabia. Methods: It is a 4-months cross-sectional survey of patient and basic knowledge of medicines. The survey consisted of two-part, demographic information and second part forty-nine questions divided into four domains. It included domain 1: Primary or essential information about patient medication, domain 2: patient information about the drug-related problem, domain 3: patient information about drug-related cost and domain 4: patient perception of medications. Medline Plus health information and DailyMed-INH elements information from National Institute of Health United State of America were used. The 5-point Likert response scale system was used. The questions were open and closed-ended. The survey distributed through social media and at 500-bed pediatrics and maternity hospital in Asir region, at ambulatory care pharmacy. The hospitals were accredited by Saudi Center for Healthcare organization (CBAHI) and Joint Commission on Hospital Accreditation from the United States of America (USA). The authors did the patients interview with electronic survey documentation. The survey was made in an electronic format and it analyzed domain three patient information about drug-related cost through survey monkey system. Results: The total responders were (614) patients with Saudi 564 (96.1%) and Non-Saudi 23 (3.9%) nationalities. The gender distribution 523 (85.2%) were females and 91 (14.8%) were males. The most type of medications used was anti-diabetic and anti-hypertension medicines, Skin medications and drugs for Respiratory Diseases. The responders showed good knowledge about drug storage at room temperature 380 (64.7%) or refrigerator 378 (64.7%), protect medication from light exposures 335 (57.56%) and how to behave with an expired medication 328 (59.85%). The patient had not adequate information about prescription prices 294 (49.83%) and imperfect knowledge about Health insurance coverage of medications 198 (32.53%). The patients showed that missing of medication knowledge led them to visit doctor clinic 114 (20%), visit the pharmacy 180 (32.4%), visit hospital emergency 40 (7.4%), hospital admission 77 (13.9%) or intensive care admission 23 (4.3%). Conclusion: The patients missed medication cost knowledge in Ministry of Health organization. Drug-related prices and medication cost awareness are demanding for Saudi patient to prevent drug-related hospital admission, patient’s shares in the drug therapy plan to choose the appropriate medications to improve patient adherence and improve clinical outcomes and patients’ quality of life.
Keywords: Patient; Knowledge; Medications; Cost; Ministry of Health; Saudi Arabia